Mergers and acquisitions in China (Sweet & Maxwell Asia,West Group, 2007)
Mergers and acquisitions in China will provide us with Stamford law corporation's useful knowledge and practical experience. It is a comprehensive guide to the legal framework, forms and structures of mergers and acquisitions transactions, government approval and due diligence processes,...